Clinical factors associated with developmental delay in placental abruption - Eun Hui Joo; Nari Kim; Hyun Mee Ryu; Sang Hee Jung; Eun Hee Ahn; Ji Yeon Lee (Frontiers in Medicine, 2025)
BackgroundThis study aimed to investigate the association between clinical characteristics and neonatal developmental delay (DD) in women with placental abruption (PA).MethodsWe retrospectively reviewed obstetric characteristics and perinatal outcomes of singleton pregnancies complicated by PA who were healthy before pregnancy between 2010 and 2021. Neuromotor development was evaluated using Bayley Scales of Infant and Toddler Development, Third Edition, and/or Gross Motor Function Measure. Clinical characteristics were compared between offspring with and without developmental delay to identify associated risk factors.ResultsAmong 9,374 deliveries, 188 cases (2.0%) were diagnosed with PA, and 33 infants exhibited developmental delay. Maternal demographics, including age, body mass index (BMI), nulliparity, and history of preterm birth, did not differ significantly between groups. Prenatal ultrasound suspected PA in 16.4% of cases in the developmental delay group and 18.2% in the no-delay group. However, a longer interval between diagnosis and delivery [adjusted OR (aOR) = 9.82; 95% CI, 1.25–77.24; P = 0.030] and delivery before 32 weeks' gestation (aOR = 19.65; 95% CI, 1.46–264.40; P = 0.025) were significantly associated with developmental delay.ConclusionUltrasound findings suggestive of PA were not associated with developmental delay in offspring. However, a prolonged diagnosis-to-delivery interval and extreme prematurity were significant risk factors. These findings underscore the limitations of ultrasound in detecting clinically significant PA and highlight the importance of timely clinical decision-making. Further research is warranted to improve diagnostic strategies for PA.